2015
DOI: 10.1590/1519-6984.17513
|View full text |Cite
|
Sign up to set email alerts
|

Planktonic production and respiration in a subtropical lake dominated by Cyanobacteria

Abstract: Planktonic primary production and respiration rates were estimated in a subtropical coastal lake dominated by Cyanobacteria in order to investigate the temporal and vertical variation in this lake and to evaluate its relationships with limnological variables and phytoplankton. Light and dark bottles were incubated at four different depths in the central part of the lake and were performed bimonthly from June/2009 to December/2010. No significant difference was evident among depths in relation to phytoplankton,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Our results also confirm previous findings using bottles incubation, where the highest primary production was recorded at subsurface, decreasing with depth (Tonetta et al, 2015b). Furthermore, the authors presented that the highest respiration rates occurred at 1.0 m depth, and did not increase with depth, showing a more homogeneous condition to the pelagic 6.…”
Section: Vertical and Horizontal Variability In Metabolic Ratessupporting
confidence: 92%
“…Our results also confirm previous findings using bottles incubation, where the highest primary production was recorded at subsurface, decreasing with depth (Tonetta et al, 2015b). Furthermore, the authors presented that the highest respiration rates occurred at 1.0 m depth, and did not increase with depth, showing a more homogeneous condition to the pelagic 6.…”
Section: Vertical and Horizontal Variability In Metabolic Ratessupporting
confidence: 92%
“…Peri Lake is predominantly CO 2 supersaturated (Tonetta et al 2015;Fontes et al 2015;and this study) with at least one period of influx (summer). The pCO 2 concentrations and CO 2 flux can also be regulated by meteorological factors such as turbulence in the water column caused by advection or wind shear (MacIntyre et al 2010;Read et al 2012).…”
Section: Discussionmentioning
confidence: 82%
“…Zhang et al [24] observed that maximum growth occurred at 0.3 m of the water column for diatoms, chlorophytes, and cyanobacteria which decreased as irradiance increased in Lake Taihu, China. Similarly, in Peri Lake, Brazil, a higher primary production rate of the toxic cyanobacteria species Cylindrospermopsis was found at the surface and decreased as a function of water column depth [25]. In addition, the thermal gradient and mixing which causes stratification in the water column is also reported to influence the seasonal composition of phytoplankton by controlling the nutrient distribution in the water column [21].…”
Section: Introductionmentioning
confidence: 93%
“…Cyanobacteria species may gain dominance by using gas vesicles, which enable them to regulate their buoyancy, for vertical movement in the water column to track for light, nutrients, and favorable water temperature [24]. These gas vesicles have notable similarities in molecular structure amongst cyanobacterial genera, but they differ in shape, yield, and critical pressures, with Microcystis having a more stable gas vesicle compared to others [25]. It is reported that the optimal habitat for phytoplankton growth is at a depth of 3 m to 5 m within the water column [20].…”
Section: Introductionmentioning
confidence: 99%